The Effect of Monetary Policy on Inflation: an Empirical Approach (Nomico, 2025)
This study explores the impact of monetary policy on inflation rate, focusing on the role of interest rates, money supply, and bank credit. Using a quantitative approach, this research analyzes how these variables influence inflation through statistical methods. The study employs multiple linear regression analysis to determine the relationships between the independent and dependent variables. Secondary data from official financial reports and economic publications provide the basis for analysis. The findings suggest that interest rates have a negative relationship with inflation, meaning an increase in interest rates can help reduce inflationary pressures. Meanwhile, money supply and bank credit have a positive relationship with inflation, indicating that higher liquidity and credit availability contribute to rising inflation. The statistical tests confirm that the model used is valid and reliable, ensuring accurate interpretations of the results. This study underscores the importance of monetary policy adjustments in maintaining price stability. Policymakers should carefully manage interest rates, money supply, and credit distribution to effectively control inflation and promote economic stability.